Estudo sobre a liderança feminina em cargos diretivos de associações e clubes desportivos na Região Autónoma da Madeira - Sara Ribeiro Guedes (2017)
The purpose of this study is to analyse and characterize female presence in sport's associative movement in Madeira Autonomous Region (MAR). In order to analyse the female presence in the sport's associative world in MAR, the research was divided into two studies. The first study has the objective to do the analysis and characterization of the female presence in the associative movement in the region. The second study has the purpose to characterize the profile of the leaders of the associative movement in the MAR regarding gender. Both studies brought us to the awareness of the low female presence in the sector, with a percentage of only 13% women, being this figure even lower at the presidency level (12.5%). The weak female presence in associative sports management is even less justifiable when analysing the qualifications and hours of dedication, being that there are no significant differences compared whit the male gender.